1999
DOI: 10.1002/etc.5620180916
|View full text |Cite
|
Sign up to set email alerts
|

Differences in neurobehavioral responses of chinook salmon (Oncorhynchus tshawytscha) and rainbow trout (Oncorhynchus mykiss) exposed to copper and cobalt: Behavioral avoidance

Abstract: Abstract-Behavioral avoidance of copper (Cu), cobalt (Co), and a Cu and Co mixture in soft water differed greatly between rainbow trout (Oncorhynchus mykiss) and chinook salmon (O. tshawytscha). Chinook salmon avoided at least 0.7 g Cu/L, 24 g Co/L, and the mixture of 1.0 g Cu/L and 0.9 g Co/L, whereas rainbow trout avoided at least 1.6 g Cu/L, 180 g Co/L, and the mixture of 2.6 g Cu/L and 2.4 g Co/L. Chinook salmon were also more sensitive to the toxic effects of Cu in that they failed to avoid Ն44 g Cu/L, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 22 publications
2
55
0
2
Order By: Relevance
“…Olfactory neurons possess a unique capacity to regenerate, a property that has been used to reveal the cellular component of olfaction in fish (4), amphibians (5), snakes (6), birds (7), and mammals (8,9). Furthermore, some chemicals, such as heavy metals and pesticides, even at sublethal concentrations, are able to disturb a broad range of olfaction-dependent behavior and cause long-lasting damage to the sensory epithelium (10)(11)(12); this has been used to provoke degeneration and regeneration of olfactory neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory neurons possess a unique capacity to regenerate, a property that has been used to reveal the cellular component of olfaction in fish (4), amphibians (5), snakes (6), birds (7), and mammals (8,9). Furthermore, some chemicals, such as heavy metals and pesticides, even at sublethal concentrations, are able to disturb a broad range of olfaction-dependent behavior and cause long-lasting damage to the sensory epithelium (10)(11)(12); this has been used to provoke degeneration and regeneration of olfactory neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonid fishes tend to avoid relatively low concentrations of copper, whereas at high concentrations fish become anosmic (10). Chronic exposure to copper causes impaired avoidance of conspecific alarm cues in Iowa darters (Etheostoma exile) (15) and Colorado pike minnows (Ptychocheilus lucius) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have illustrated the sensitivity of olfaction to toxicants, including cadmium (Brown et al, 1982;Stromberg et al, 1983), copper (Hara et al, 1976;Brown et al, 1982;Rehnberg and Schreck, 1986;Julliard et al, 1995;Hansen et al, 1999), diazinon (Moore and Waring, 1996) and mercury (Hara et al, 1976;Brown et al, 1982;Rehnberg and Schreck, 1986). It has recently become apparent that olfactory disruption by sublethal toxicant exposure may consequently disturb olfaction-mediated predator avoidance behaviours of fish.…”
mentioning
confidence: 99%
“…Many studies have demonstrated that morphological alterations induced by several aquatic contaminants (generally heavy metals and pesticides, but also detergents) are accompanied by reduced electric activity, recordable as electroolfactogram (EOG) or electroencephalogram (EEG), in the ORC and olfactory bulb respectively (Bardach et al 1965, Sutterlin et al 1971, Hansen et al 1999b). Other studies have confirmed the relationship between the impairment of olfactory discrimination and behaviour (Rehnberg & Schreck 1986, Hidaka & Tatsukawa 1989, Saglio & Trijasse 1998, Hansen et al 1999a). Detergents at sublethal doses are in fact able to affect feeding behaviour, conspecific attraction, and locomotory activity (Bardach et al 1965, Olsén & Höglund 1985, Barbieri et al 1998.…”
Section: Discussionmentioning
confidence: 70%